2011
DOI: 10.1016/j.jbi.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Communication and team situation awareness in the OR: Implications for augmentative information display

Abstract: Team Situation Awareness (TSA) is one of the critical factors in effective Operating Room (OR) teamwork and can impact patient safety and quality of care. While previous research showed a relationship between situation awareness, as measured by communication events, and team performance, the implications for developing technology to augment and facilitate TSA were not examined. This research aims to further study situation-related communications in the cardiac OR in order to uncover potential degradation in TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 41 publications
1
75
0
1
Order By: Relevance
“…A study by Parush et al (2011) observed surgical teams performing ten open-heart surgeries to investigate the communicative processes by which SA was developed and maintained within surgical teams. The researchers focused on speech acts in which situation-related information was shared among the team.…”
Section: Information Sharingmentioning
confidence: 99%
“…A study by Parush et al (2011) observed surgical teams performing ten open-heart surgeries to investigate the communicative processes by which SA was developed and maintained within surgical teams. The researchers focused on speech acts in which situation-related information was shared among the team.…”
Section: Information Sharingmentioning
confidence: 99%
“…A csapatmunka hiányosságai számos okra vezethetők vissza, amelyek között szerepet játszik a csapattagok in tézményi státusza, hierarchiában elfoglalt helye, a hibák és tévedések kezelése, egyéni tényezők sora (nemi kü lönbségek, stressztolerancia), valamint több külső ténye ző is (felszereltség, intézményi jellemzők) [13]. A hibás kommunikációs mechanizmusok (például a le nem zárt vagy késleltetett információcsere) számos lényeges, gyak ran életfontosságú információveszteségért tehetők fele lőssé [14]. A betegbiztonság és a hatékony együttműkö dés érdekében szervezett tréningek -mint például a Sawyer és kutatótársai [15] által létrehozott Team STEPPS (Team Strategies and Tools to Enhance Perfor mance and Patient Safety) program -gördülékenyebbé teszik a csapatmunkát, pozitív szerkezeti változásokat indukálnak, serkentik a kölcsönös támogatás rendszeré nek kialakítását, és javítják a csapattagok közötti kommu nikációt.…”
Section: öSszefoglaló Közleményunclassified
“…The fields of human factors and human-computer interaction have employed various means to augment clinical settings for teams [11], [23], [24], [25], [26], [27]. France et al [28] found electronic whiteboard use reduces physician workload in an ED, resulting in fewer workflow interruptions.…”
Section: B Technology Interventions For Improved Samentioning
confidence: 99%